Using Experimentation Method to Improve Children's Science Skills - Wa Ode Endriyani; Muamal Gadafi; Nurhayati (FKIP Universitas Halu Oleo, 2024)
The purpose of this study was to improve children's scientific skills by using experimental methods in Group B of Bungi Indah Kindergarten, Konawe Regency. This type of research is classroom action research. This research was conducted in two cycles. Each stage of this research follows the classroom behavior procedure. They are: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. Observation and interview were used as data collection techniques. The data analysis technique is descriptive. The subjects of this study were 15 children aged 5-6 years, 4 girls and 11 boys, in Group B TK Bungi Indah Konawell Regency. Based on data analysis of the observation of teacher teaching activities in Cycle I, the success rate was 80%, the results of children's learning activities in Cycle I were 80%, and the learning outcomes of children in Cycle I were 60%. In Cycle II the success rate of teacher teaching activities reached 93.33%, Cycle II children's learning activities reached a success rate of 93.33%, and Cycle II student learning outcomes reached a success rate of 93.33%. achieved. Therefore, it can be concluded that this research can improve cognitive performance with experimental methods in Group B children of Bungi Indah Kindergarten, Konawe Regency